Formação metropolitana: a Grande Vitória (1995-2005) - Almeida, Rita de Cássia Barcellos (2009)
The present dissertation is focused on the “metropolitan formation”, considering the Metropolitan Region of Great Vitoria as a case study. The object of study comprehends the historical trajectory of the capixaba metropolitan reality, its institutionalization and consequences. The research takes into consideration the economic modernization of Espirito Santo state and its outcomes. The research analyzes the cities formation context, particularly the metropolization process and its specificities. The comprehended period is between 1995, date of institutionalization of the Metropolitan Region of Great Vitoria, until 2005. The analysis consists in specifying the origins and delimitating the evolution process of the formation of the Metropolitan Region of Great Vitoria and also registering the current reality of the area, pursuant to the consolidation of modernity. The research is justified for the insufficiency of local historiography related to the formation of the Metropolitan Region of Great Vitoria, that before its legal constitution in the nineties, could be categorized as a large urbanized extension capable of combining growth with social differences and still promote a spatial concentration of poverty.